Use the substitution method to solve the system of equations below.
y = 3x
-2x + 8y = -22

x = 1
y = -3

x = -1
y = 3

x = -1
y = -3

x = 1
y = 3

Respuesta :

Answer:

  • x = -1
  • y = -3

Step-by-step explanation:

Since you have an expression for y, it is convenient to use it.

  -2x + 8(3x) = -22 . . . . . substitute 3x for y in the second equation

  22x = -22 . . . . . simplify

  x = -1 . . . . . . . . . .divide by 22

Substituting this value into the expression for y:

  y = 3(-1) = -3

The solution is (x, y) = (-1, -3).

ACCESS MORE